Brazing Strategies for High Temperature Ultrasonic Transducers Based on LiNbO3 Piezoelectric Elements - Christopher Bosyj (Instruments, 2018)
Long-term installation of ultrasonic transducers in high temperature environments allows for continuous monitoring of critical components and processes without the need to halt industrial operations. Transducer designs based on the high-Curie-point piezoelectric material lithium niobate have been shown to both be effective and stable at extreme temperatures for long-term installation. In this study, several brazing techniques are evaluated, all of which aim to provide both mechanical bonding and acoustic coupling directly to a bare lithium niobate piezoelectric element. Two brazing materials—a novel silver-copper braze applied in a reactive air environment and an aluminum-based braze applied in a vacuum environment—are found to be suitable for ultrasound transmission at elevated temperatures. Reliable wide-bandwidth and low-noise ultrasound transmission is achieved between room temperature and 800 °C.